Robust beamforming design for multiple-input–single-output secrecy multicasting systems with simultaneous wireless information and power transmission - Zhu, Zhengyu; Chu, Zheng; Wang, Zhongyong; Cui, Jianhua (IET communications, 2016)
In this study, the authors study simultaneous wireless information and power transfer for multiuser multiple-input–single-output secure multicasting channels with imperfect channel state information. First, a robust secure beamforming design is considered, where the transmit power is minimised subject to the secrecy rate outage probability constraint for legitimate users and the harvested energy outage probability constraint for energy harvesting receivers. The original problem is non-convex due to the presence of the probabilistic constraints. By utilising Bernstein-type inequalities, the authors transform the outage constraints into the deterministic forms. In order to identify a local optimal rank-one solution, the authors propose an efficient approach based on a constrained concave convex procedure method to convert the original problem into a sequence of convex programming problems. Finally, simulation results are provided to validate the performance of the proposed design methods.